2005
DOI: 10.1619/fesi.48.113
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Formal Solutions of Nonlinear First Order Singular Partial Differential Equations in Complex Domain

Abstract: Abstract. This paper is a continuation of our early paper [MS]. In this paper, we study the structure of formal power series solutions of a first order nonlinear partial di¤erential equation which is defined and holomorphic in a neighborhood of the origin of several complex variables. Our main theorem (Theorem 1.1) characterizes the convergence or the divergence of a given formal power series solution a priori. Especially, in the case of divergence, we give the rate of divergence in terms of Gevrey index which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…On the other hand, M. Miyake and A. Shirai [2,3] In this paper we shall extend a part of results of [2] in the case of ordinary di¤erential equations. Precisely, in [2] for the criterion of convergence or divergence of formal solution the Taylor coe‰cients of first order of formal solution and equation are used, but in this paper the Taylor coe‰cients of higher order are used.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, M. Miyake and A. Shirai [2,3] In this paper we shall extend a part of results of [2] in the case of ordinary di¤erential equations. Precisely, in [2] for the criterion of convergence or divergence of formal solution the Taylor coe‰cients of first order of formal solution and equation are used, but in this paper the Taylor coe‰cients of higher order are used.…”
Section: Introductionmentioning
confidence: 79%
“…To this equation, a lot of Maillet type theorems have been studied by many mathematicians. For example, Gérard-Tahara, and Miyake-Shirai study the nonlinear case, which is found in the book or papers [4,6,7] and [8]. They obtained the Maillet type theorem, which include the convergent case.…”
Section: Related Resultsmentioning
confidence: 99%
“…As for existence of analytic solutions in [7], [8], [9], they firstly constructed a solutions of formal power series and next showed the convergence under a condition called Poincaré's condition, which is essential to show the convergence. In this paper F ðx; u; pÞ is real valued, so Poincaré's condition is as follows: Definition 1.4.…”
Section: Notations Definitions and Theoremsmentioning
confidence: 99%
“…However, if Under the condition that F ðx; u; pÞ is an analytic function, there are several reseaches about F ðx; u; u x Þ ¼ 0 with (0.2). For example, its solutions of formal power series, existence of asymptotic or analytic solutions were studied by using analytical functions methods ( [1], [4], [6], [7], [8], [9] and [10] etc. )…”
Section: Introductionmentioning
confidence: 99%